Analisis Determinasi Minat Menggunakan Produk Tabungan Haji di Bank Muamalat Indonesia - Rosyad, Fakhranisahla Khalisa (ITB AAS INDONESIA Surakarta, 2024)
The rising cost of Hajj in Indonesia has become an obstacle for most Indonesian Muslims in performing the pilgrimage. Even so, several banks, including Bank Muamalat, which is a pioneer of Islamic banks in Indonesia, have acted as facilitators to help overcome this obstacle, allowing Muslims to continue to perform the pilgrimage.The purpose of this study is to determine and explain the effect of promotion, brand image, religiosity, consumer attitudes, subjective norms, and behavioral control on interest in using Bank Muamalat's Hajj savings products. The population in this study is the Jabodetabek Muslim community. Sampling with purposive sampling. This study amounted to 150 respondents with the criteria of the Jabodetabek Muslim population from the age of 17 years and knowing the Bank Muamalat Hajj savings. The approach used is quantitative with data analysis techniques Partial Least Square version 3.0. The results showed that promotion, brand image, religiosity, consumer attitudes, and subjective norms have a significant effect on interest, while behavioral control has no significant effect on interest. It is hoped that with this research, Bank Muamalat can develop Bank Muamalat's Hajj savings products.